GSD 08 platformb[a year of research through studio work, theses, exhibitions, and conferences at the Harvard University Graduate School of Design] - Kubo, Michael; Ortega, Lluis (Harvard, 2008)
Formulates prevalent tendencies and coherences within the Harvard Graduate School of Design. This book's content groupings are the site of relations between a diverse range of projects and research, developing affinities between projects, events, and writings, revealing a cross-section of ideas and interests